Multivariate analysis of phenological, pomological and fruit quality characters in apricot (Prunus armeniaca) grown in trans-Himalayan Ladakh region, India - KOREKAR, GIRISH; YADAV, ASHISH; KUMAR, RAJ; SRIVASTAVA, RAVI B; STOBDAN, TSERING (The Indian Journal of Agricultural Sciences, 2013)
The purpose of this study was to contribute to the phenological, pomological characteristics and fruit qualityspecification of 17 apricot genotypes grown under similar cultural practices in trans-Himalayan Ladakh region. A total of27 characters were analyzed during the two years of study course. A wide variation in bud break season, blossom season, harvest season, fruit size, stone mass, TSS and total acidity was observed. Except for one genotype, fruit weight from all other genotypes were determined